1995
DOI: 10.1111/1523-1747.ep12312500
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 as a New Melanogen: Coordinated Expression of Its Gene and the Tyrosinase Gene in UVB-Exposed Human Epidermis

Abstract: We previously demonstrated that human keratinocytes produce and secrete endothelins (ET), which can be strong mitogens for human melanocytes. Ultraviolet B (UVB) exposure highly stimulated the paracrine linkage of endothelins between keratinocytes and melanocytes, indicating that they are keratinocyte-derived intrinsic mitogens in UVB-induced pigmentation. In this study, the role of ET-1 as a melanogen in UVB melanogenesis was investigated in vitro and in vivo. In the conditioned medium of keratinocytes expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
215
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(220 citation statements)
references
References 17 publications
4
215
0
1
Order By: Relevance
“…DAG has been reported to activate MAPK via protein kinase C. The action of ET-1 is transmitted to stimulate cell proliferation mainly via MAPK. 9,20) The present study showed that the extract of A. officinalis did not affect the intracellular signal transduction pathway located upstream of calcium mobilization, i.e., the binding of ET-1 to the ET B R on NHMC or the production of IP 3 . In contrast, the ET-1-induced activation of MAPK was inhibited by the extract.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…DAG has been reported to activate MAPK via protein kinase C. The action of ET-1 is transmitted to stimulate cell proliferation mainly via MAPK. 9,20) The present study showed that the extract of A. officinalis did not affect the intracellular signal transduction pathway located upstream of calcium mobilization, i.e., the binding of ET-1 to the ET B R on NHMC or the production of IP 3 . In contrast, the ET-1-induced activation of MAPK was inhibited by the extract.…”
Section: Discussionmentioning
confidence: 51%
“…However, it may be very difficult for such agents to reach the melanosomes 22) in which tyrosinase acts at a sufficient dose to be effective. On the other hand, since ET-1 has been reported to promote transcription of tyrosinase, 3) this extract might inhibit tyrosinase function by inhibiting its activation The extract at concentrations of 0.01-0.5% was added to NHKC and the cells were cultured for 2 d. The amount of ET-1 secreted into the culture medium was analyzed by ELISA, as described in Materials and Methods. The values reported are meansϮS.E.M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of ET B receptors by ET-1 promotes proliferation of melanogenic precursor cells and inhibits their differentiation, two characteristic features of melanoma genesis [11]. Furthermore, ET-1 mediates ultraviolet light-induced melanin synthesis in human melanocytes [12]. In melanocytes and melanoma cells, ET-1 increases the expression of the melanoma invasion promoter MCAM (melanoma cell adhesion molecule) while decreasing expression of the melanoma invasion suppressor E-cadherin [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A few of these cytokines are known mitogens for human melanocytes, including basic fibroblast growth factor, SCF, granulocyte-macrophage colony-stimulating factor, hepatocyte growth factor, and ET-1. [42][43][44][45][46] Several cytokines, such as IL-1␣ and TNF-␣, significantly increase the expression of SCF protein by cultured human keratinocytes. 5 Accordingly, MIF may induce PAR-2 to mediate cutaneous pigmentation by increasing both the uptake of melanosomes by keratinocytes and the release of SCF, which stimulates melanogenesis.…”
Section: Discussionmentioning
confidence: 99%